(untitled) (Res Medica, 2014)
All I have to say comes from prospective studies of ischaemic heart disease made in America and in this country since World War II. In Framingham, as in the other surveys, all those who already had signs of ischaemic heart disease were put aside, and the great majority who showed no evidence of it were followed up over the years. More men than women developed the disease during middle age. In this age group, there are three main manifestations of ischaemic heart disease - sudden death, classical myocardial infarction, and angina pectoris. When the total picture in Framingham was divided up according to these different modes of presentation, they found that in those who develop angina pectoris without classical infarction there is some excess of males in the thirties; near equality in the forties; in their fifties more women were affected than men. Many of these people of course do not come for medical care, they have these symptoms but ignore them.